At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
1x + 5y = 19 ⇒ 3x + 15y = 57
3x - 6y = -6 ⇒ 3x - 6y = -6
21y = 63
21 21
y = 3
3x - 6(3) = -6
3x - 18 = -6
+ 18 + 18
3x = 12
3 3
x = 4
(x, y) = (4, 3)
It is consistent and dependent.
3x - 6y = -6 ⇒ 3x - 6y = -6
21y = 63
21 21
y = 3
3x - 6(3) = -6
3x - 18 = -6
+ 18 + 18
3x = 12
3 3
x = 4
(x, y) = (4, 3)
It is consistent and dependent.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.